Quality of life of patients undergoing cancer treatment in B. P. Koirala memorial cancer hospital, Bharatpur, Chitwan - Pandey, Radha Acharya (Kathmandu University School of Medical Science, 2014)
Abstract: Background: In patients with different type of cancers and the quality of life (QoL) improvement is the main goal, since survival can be prolonged marginally. A diagnosis is very stressful for people, affecting all aspects of their being and quality of life. Up to date, knowledge on QoL impairments throughout the entire treatment process, often including several treatment modalities is scarce. One objective of this study was to assess the quality of life of cancer patient undergoing cancer treatment. Methods: A quantitative, cross-sectional, descriptive, design was adapted. The totals of Two Hundred and Forty Five cancer patients met the inclusion criteria and were enrolled in the studies who were attending the hospital for cancer treatment during August-September, 2013. The data was collected by interview, using modified, structured scale of European Organization for Research and Treatment of Cancer Quality of life Questionnaire Core 30 (EORTC QLQ- C30), prepared by the EORTC group. Information about the patient's disease condition and treatment were obtained from the patient's medical records. The collected data was analyzed by using SPSS version 16. Descriptive and inferential statistics were used to describe the respondent's quality of life (QoL) scores and to identify the factors affecting it respectively. Results: The study findings revealed the quality of life of cancer patients to be influenced by many factors such as: site of cancer, stage of cancer, time elapsed since diagnosis and ECOG performance status. The average QoL scores (out of 100) for different scales were 85.54 (global health/QoL), 77.03 (functional), and 16.14 (symptom). Loss of appetite was the most frequent complaint (mean = 20.27) and was present in almost all the patients. As the overall QoL of the patients was significantly correlated with different QoL scales as:, cognitive, emotional, physical, social, role functioning, pain, fatigue, dyspnoea, loss of appetite and nausea/vomiting and financial problem. Conclusion: Hence, in average, the quality of life of cancer patients was found to be relatively better, although there were higher ratings for some (as: cognitive, physical, role and emotional functioning) and lower for others (like social functioning). Additional research should be done in this area for improving the quality of life of specific type of cancer patients in Nepal, though the findings of this study are expected to provide the baseline knowledge regarding it.